Biocrust cyanobacterial composition, diversity, and environmental drivers in two contrasting climatic regions in Brazil - Machado de Lima, Náthali Maria [UNESP]; Muñoz-Rojas, Miriam; Vázquez-Campos, Xabier; Branco, Luis Henrique Zanini [UNESP] (Elsevier, 2021)
Biological soil crusts or biocrusts have critical ecological roles in dryland ecosystems including soil stabilization, erosion control and nutrient cycling. Global environmental changes are expected to impact terrestrial ecosystems, including biocrust communities. Thus, a growing number of studies have focused on investigating the diversity of biocrust-forming organisms including cyanobacteria. Despite the increasing interest in understanding biocrust cyanobacteria, there are still several knowledge gaps, particularly in areas from South America, where studies are limited. Here, we studied the composition, abundance, and environmental drivers of cyanobacterial biocrust from two important biomes in Brazil, i.e. Caatinga and Pampa, which are subject to desertification and anthropogenic pressures, respectively. Ten samples at three sites were explored at each biome (n = 60) and cyanobacterial biocrust community composition and diversity was analyzed through morphological evaluation and Next Generation Sequencing targeting the 16S rRNA gen. Soil and climatic variables, e.g. organic matter, soil texture, nitrogen and phosphorus content, temperature, and solar irradiance, were also determined at each site. Our results showed that biocrust cyanobacteria had distinct taxonomic compositions and assemblages at each biome. Similarly, cyanobacterial composition across sites within each biome differed substantially. Soil temperature and pH were identified as the main factors explaining such biotic structures. Caatinga sites, characterized by more arid environments, presented a higher abundance of N-fixing cyanobacteria, e.g. Scytonema. In contrast, Pampa, with higher rainfall regimes, showed a larger abundance of biocrust-forming bacteria such as Microcoleus and Leptolyngbya. The outcomes of this research are expected to provide a basis to enhance biocrusts and conservation efforts and promote the use of biocrust cyanobacteria as global change indicators.
Keywords: 16S rRNA; Biocrust; Caatinga; Cyanobacterial diversity; Pampa; Scytonema